Modulation of Oligodendrocyte Differentiation by Mechanotransduction - Lourenço, Tânia; Grãos, Mário (Frontiers in Cellular Neuroscience, 2016)
Oligodendrocytes (OLs) are responsible for the myelination of axons in the central nervous system (CNS). The differentiation of OLs encompasses several stages, through which cells undergo dramatic biochemical and morphological changes. OL differentiation is modulated by soluble factors (SFs)—such as growth factors and hormones—, known to be essential for each maturation stage. Besides SFs, insoluble factors such as extracellular matrix (ECM) proteins and other microenvironmental elements also play a pivotal role during OL differentiation. Recently, a growing number of studies were published concerning the effect of biophysical properties of the extracellular milieu on OL differentiation and myelination, showing the importance of ECM stiffness and topography, strain forces and spatial constraints. For instance, it was shown in vitro that OL differentiation and maturation is enhanced by substrates within the reported range of stiffness of the brain and that this effect is potentiated by the presence of merosin, whereas the myelination process is influenced by the diameter of axonal-like fibers. In this mini review article, we will discuss the effect of mechanical cues during OL differentiation and the possible molecular mechanisms involved in such regulation.